Pension Fund Investment in Forestry - Binkley, Clark S.; Stewart, Fiona; Power, Samantha (World Bank, Washington, DC, 2021)
A forestry investment can include land suitable for growing trees, the trees themselves, or both. Forestry has long provided opportunities for institutional investors but the scope for this investment remains limited. Forestry investment can offer financial and environmental, social, and governance (ESG) benefits. However, challenges to investing in forestry are significant particularly in emerging markets, which is also where reforestation, afforestation, and sustainable forest management is most needed. Currently, there is a lack of both knowledge about and interest in the forestry asset class. This report addresses this by detailing the nature of forestry investments, explores the case for investing in forestry, explains the mechanics of forestry investments, and highlights some of the challenges. The report concludes that the time is right to support broader involvement by pension plans in forestry investments globally.